2020
DOI: 10.1038/s41598-020-73684-y
|View full text |Cite
|
Sign up to set email alerts
|

Skin hydration dynamics investigated by electrical impedance techniques in vivo and in vitro

Abstract: Skin is easily accessible for transdermal drug delivery and also attractive for biomarker sampling. These applications are strongly influenced by hydration where elevated hydration generally leads to increased skin permeability. Thus, favorable transdermal delivery and extraction conditions can be easily obtained by exploiting elevated skin hydration. Here, we provide a detailed in vivo and in vitro investigation of the skin hydration dynamics using three techniques based on electrical impedance spectroscopy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 49 publications
1
36
0
Order By: Relevance
“…The results in our study showed that baseline skin impedance at the abdomen was significantly higher than at the upper arm across all subjects, and within the Latino and black self-identified racial/ethnic groups. This higher impedance at the abdomen may be due to the lower skin hydration observed at the abdomen when compared to the upper arm and volar forearm, as studies have shown that increased skin hydration may lead to increased skin permeability and consequently a decrease in skin membrane electrical resistance [26][27][28].…”
Section: Baseline Epidermal Propertiesmentioning
confidence: 99%
“…The results in our study showed that baseline skin impedance at the abdomen was significantly higher than at the upper arm across all subjects, and within the Latino and black self-identified racial/ethnic groups. This higher impedance at the abdomen may be due to the lower skin hydration observed at the abdomen when compared to the upper arm and volar forearm, as studies have shown that increased skin hydration may lead to increased skin permeability and consequently a decrease in skin membrane electrical resistance [26][27][28].…”
Section: Baseline Epidermal Propertiesmentioning
confidence: 99%
“…After 2 h, the Finn Chambers were removed, and the skin surface was gently wiped with a sterile cotton tissue. The reason for employing 2 h as the sampling time was to enable sufficient skin hydration [40], as well as adequate time for extraction of analytes, such as Trp and Kyn [33], while at the same time we were able to avoid an extensively long sampling time for practical reasons. Preliminary in vivo studies performed with CHI, where the sampling time was varied between 0.5 h, 2 h, 4 h, and 8 h, indicated that the amounts increased linearly over time.…”
Section: Study Protocolmentioning
confidence: 99%
“…This work will enable better electrode designs and will be beneficial to several applications. In the fields of cosmetics and drug delivery, it will allow to improve upon current methods used to investigate and characterize SC hydration [29,30]. For example, it has been experimentally reported that some types of electrodes exhibit better performances when measuring either very hydrated or very dry skin, without providing theoretical explanations for such results [31,32].…”
Section: Electrode Dimension Sensitivitymentioning
confidence: 99%